F.R. David : Flurry. - Holder, Will; Lorde, Audre; Chomsky, Noam; Klemperer, Victor; McNeill Whistler, James Abbott; Weiner, Lawrence; Fuchs, Rudi; Finlay, Ian Hamilton; Dillard, Annie; Delaney, C.F.; Notley, Alice; Lloyed, Genevieve; et al. ([s.l.] : uh books, 2018)
McLuskey, Emmie ; Gruijthuijsen, Krist ; Dietrich, Maurin ; Knox, Bitsy ; Leaver-Yap, Mason ; Pageard, Camille ; Paulich, Bert ; Stark, Frances ; Verbeke, Pieter
boek